If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -2 = 10x + 1 Reorder the terms: -2 + 2x = 10x + 1 Reorder the terms: -2 + 2x = 1 + 10x Solving -2 + 2x = 1 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -2 + 2x + -10x = 1 + 10x + -10x Combine like terms: 2x + -10x = -8x -2 + -8x = 1 + 10x + -10x Combine like terms: 10x + -10x = 0 -2 + -8x = 1 + 0 -2 + -8x = 1 Add '2' to each side of the equation. -2 + 2 + -8x = 1 + 2 Combine like terms: -2 + 2 = 0 0 + -8x = 1 + 2 -8x = 1 + 2 Combine like terms: 1 + 2 = 3 -8x = 3 Divide each side by '-8'. x = -0.375 Simplifying x = -0.375
| 8+2x=5x-13 | | n+18=7 | | 10x-x-2x-x= | | 11x+25=7x+5 | | -3x-9=2x+7 | | -7r-3+2r= | | 3(2x+2)-4=5(x+1) | | .06+0.08(100-x)=4.2 | | 11x+13y=90 | | x^2-112=20x | | -8x-4x= | | -2(2x-4)=3(-12x+24) | | 2(6x+9)= | | 8x+20+16x-8=180 | | x^2+112=20 | | 4(-2)*2=8(-2)+3(-2)+6 | | 8+15i=2ni+3ni | | -12r=52+(-4) | | x-13=-34 | | 2x+5-6(x+1)=7x-5 | | 32x+6=12x-4 | | x-3*x=40 | | 2(x+1)=6+3x | | 8x-x=-49 | | -24x+x= | | 5(-4+2y)-3y=1 | | (-16)=(-19)-w | | 14q=-21 | | 2-5a-b=4 | | (x+12)*8=4*x | | -5c=-35 | | -4(n-1)=11 |